2018
DOI: 10.1002/path.5059
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial aspects of oncogenic signalling determine the response to combination therapy in slice explants from Kras‐driven lung tumours

Abstract: A key question in precision medicine is how functional heterogeneity in solid tumours informs therapeutic sensitivity. We demonstrate that spatial characteristics of oncogenic signalling and therapy response can be modelled in precision‐cut slices from Kras‐driven non‐small‐cell lung cancer with varying histopathologies. Unexpectedly, profiling of in situ tumours demonstrated that signalling stratifies mostly according to histopathology, showing enhanced AKT and SRC activity in adenosquamous carcinoma, and mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…This indicates that it is important to investigate whether the targeted in situ biological functions are appropriately preserved during cultivation, prior to perturbation studies. Despite these findings, we showed that tumor slices can model spatial response to targeted therapies, midst drug treatments remain brief (24 h) and are initiated at the onset of culturing 26 . The following protocol describes important validation aspects relevant to the establishment and analysis of tumor slice cultures, prior to their application in pharmacological drug testing.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…This indicates that it is important to investigate whether the targeted in situ biological functions are appropriately preserved during cultivation, prior to perturbation studies. Despite these findings, we showed that tumor slices can model spatial response to targeted therapies, midst drug treatments remain brief (24 h) and are initiated at the onset of culturing 26 . The following protocol describes important validation aspects relevant to the establishment and analysis of tumor slice cultures, prior to their application in pharmacological drug testing.…”
Section: Introductionmentioning
confidence: 84%
“…2. Calculate the relative viability of the slices cultivated for different time points compared to the nearest 0 h slice as done in our previous study (Närhi et al, Figure S2B and C) 26 . Similarly, assess potential intra-slice viability gradients by quantifying viability in the top, middle and bottom section of a cultured slice, and calculate the relative viability of each section to its closest 0 h slice.…”
Section: Analysis Of Tissue Viability and Biomarker Expressionmentioning
confidence: 99%
See 3 more Smart Citations